Peningkatan Energi Metabolis Produk Fermentasi Campuran Bungkil Inti Sawit dan Dedak Padi - Sukaryana, Yana (Jurnal Penelitian Pertanian Terapan, 2010)
The research objective is to compare the metabolism energy of palm kernel cake (80%) and rice bran (20%) mix fermentation product with the same unfermented product. To compare is used Student-t test. Determination and procedure of metabolism energy refers to Sibbald and Morse (1983) developed method. The results showed that the average metabolism energy content of palm kernel cake (80%) and rice bran (20%) mix fermentation product (2149,33 ±24,90) significantly different (P<0,05) higher than palm kernel cake (80%) and rice bran (20%) mix unfermented product (1836,04 a±19.28) or an increase of 17,06%. Keywords: Palm kernel cake, rice bran, fermentation, metabolism energy.